A Framework for Fourth Industrial Revolution Adoption by Small-Scale Rural Farmers in Sub-Saharan Africa: A Systematic Literature Review - Willard Munyoka; Nkhangweni Lawrence Mashau; Modimowabarwa Kanyane (The Thinker)
Climate change is witnessed in unpredictable weather conditions that negatively affect human lives, economies, and farming worldwide. This results in severe heat waves and a shift in rainfall patterns. This is a major global threat to agriculture and food security, especially for rural farmers. Small-scale rural-based farmers contribute immensely to local communities’ socio-economic well-being and food security. However, most of the small-scale rural farmers are constrained, especially regarding resources. There is a need for the agricultural industry in rural areas to adopt the fourth industrial revolution (4IR) technologies to predict and make well-informed decisions on how to manage existing, often constrained resources efficiently. Government support, in various forms, is equally needed. Furthermore, adopting 4IR by small-scale rural farmers will assist countries in the Sub-Saharan African region in achieving the United Nations Sustainable Development Goal Number 2 on ‘Zero Hunger’ by achieving food security and promoting smart, sustainable agriculture. However, there is a deficiency in the literature on 4IR adoption frameworks to guide small-scale rural farmers in adopting 4IR tools to manage their resources and promote sustainable agriculture. This study aims to develop a 4IR adoption framework that could guide small-scale rural farmers in adopting 4IR tools for managing their resources and promoting smart agriculture. A systematic literature review approach is employed to identify critical components significant for adopting 4IR in rural farming. Rural farmers may use this framework as a guiding lens when adopting 4IR tools. This study broadens the scope of the scant literature on the best practices for adopting 4IR for smart small-scale rural farming in Sub-Saharan Africa and other developing nations with similar setups. The smart-scale rural farming is mainstreamed within the smart village concept and the greenfield or green economy resilient to harsh climate change conditions.